The homozygous p.V37I variant of GJB2 is associated with diverse hearing phenotypes. (12th April 2014) - Chai, Y.; Chen, D.; Sun, L.; Li, L.; Chen, Y.; Pang, X.; Zhang, L.; Wu, H.; Yang, T.
Abstract : The homozygous p.V37I variant of GJB2 is frequent in East Asians and has been reported to have a pathogenic role in mild‐to‐moderate hearing impairment (HI). In this study, we investigated the prevalence and phenotypic spectrum of homozygous p.V37I in three Chinese Han cohorts with severe‐to‐profound HI ( n = 857, Cohort S), mild‐to‐moderate HI ( n = 88, Cohort M) and normal hearing ( n = 1550, Cohort N). Sequencing of GJB2 showed that homozygous p.V37I was detected in 1.63% (14/857), 12.5% (11/88) and 0.32% (5/1550) of subjects in Cohorts S, M and N, respectively. It was strongly associated with both mild‐to‐moderate (p = 2.0 × 10 −11 ) and severe‐to‐profound (p = 0.001) HI, but was estimated to have a rather low penetrance (17%). Among the hearing impaired subjects with homozygous p.V37I, the onset of HI was congenital in 65% (11/17) and delayed in 35% (6/17). By targeted next‐generation sequencing of 79 known deafness genes, we identified an additional homozygous pathogenic mutation of CDH23 in 1 of 14 p.V37I homozygous subjects from Cohort S. Our study suggested that homozygous p.V37I is associated with a broader spectrum of hearing phenotypes than previously revealed. Data presented in this study can be effectively applied to clinical evaluation and genetic counseling of people carrying this variant.